Galactic Archaeology with CoRoT and APOGEE: Creating mock observations from a chemodynamical model. Issue 8 (30th September 2016) - Anders, F.; Chiappini, C.; Rodrigues, T. S.; Piffl, T.; Mosser, B.; Miglio, A.; Montalbán, J.; Girardi, L.; Minchev, I.; Valentini, M.; Steinmetz, M.
Abstract: In a companion paper, we have presented the combined asteroseismic‐spectroscopic dataset obtained from CoRoT light curves and APOGEE infra‐red spectra for 606 solar‐like oscillating red giants in two fields of the Galactic disc (CoRoGEE). We have measured chemical abundance patterns, distances, and ages of these field stars which are spread over a large radial range of the Milky Way's disc. Here we show how to simulate this dataset using a chemodynamical Galaxy model. We also demonstrate how the observation procedure influences the accuracy of our estimated ages.